Efficacy of nGVS to improve postural stability in people with bilateral vestibulopathy: A systematic review and meta-analysis - McLaren, Ruth; Smith, Paul F.; Taylor, Rachael L.; Ravindran, Shobika; Rashid, Usman; Taylor, Denise (Frontiers in Neuroscience, 2022)
Objective Noisy galvanic vestibular stimulation (nGVS) has been used to boost vestibular afferent information to the central nervous system. This has the potential to improve postural control for people for whom vestibular signals are weak, such as in bilateral vestibulopathy (BVP). The aim of this systematic review and meta-analysis is to investigate the evidence for nGVS as a modality to improve postural control in people with BVP. Methods A comprehensive systematic search was conducted of five databases up to July 2022 to find studies applying nGVS to people with BVP, with the aim of improving postural control. Two independent reviewers screened and identified eligible studies, completed a risk of bias evaluation (Cochrane) and extracted relevant data. The standardized mean difference (SMD) based on Hedges' g was calculated as a measure of effect size for the primary outcome measure that best identified postural control, and a forest plot generated. Results Seven studies met the eligibility criteria, with five being suitable for meta-analysis. Meta-analysis revealed a moderate effect in favor of nGVS improving postural control during standing and walking [pooled SMD = 0.47 95% CI (0.25, 0.7)]. nGVS-mediated improvements in postural control were most evident in observations of reduced sway velocity when standing on a firm surface with eyes closed, and in the reduced variability of gait parameters, particularly those measuring lateral stability. Conclusions Coincident nGVS in people with BVP improves postural control during standing and walking. This improvement appears to be context specific, in that vestibular augmentation is most effective in situations where visual inputs are limited, and where reliable context specific proprioceptive cues are available. Further research is warranted investigating additional circumstances in which nGVS improves postural control, including investigating the residual, and sustained effects of nGVS. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=342147, identifier: 342147.